Preparation method and application of oral ulcer antibacterial repair film
By combining needle-shaped bioactive glass microspheres with gelatin and chitosan, and preparing a repair membrane using electrospinning technology, the problem of insufficient mechanical strength of existing repair materials is solved, and the effect of efficient antibacterial, inflammation-inhibiting and improving mechanical strength is achieved, which is suitable for the repair of oral ulcers.
Patent Information
- Application Number
- CN202411980192.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing oral ulcer repair materials have insufficient mechanical strength and lack sufficient experimental verification in practical applications, making it difficult to meet the needs of high stress repair.
A needle-shaped bioactive glass microspheres are combined with gelatin and chitosan to prepare oral ulcer antibacterial repair membranes through electrospinning technology to enhance the mechanical strength and biological activity of the material.
The mechanical strength and antibacterial and anti-inflammatory properties of the repair membrane are improved, and are suitable for oral repair areas that need to withstand high stress, and their effectiveness has been verified through experiments.
Smart Images

Figure CN119770720A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and more specifically, relates to a preparation method and application of an oral ulcer antibacterial repair film. Background Art
[0002] Oral ulcer is a common oral mucosal disease, which can be caused by microbial infection, immune factors, trauma, etc. This disease is characterized by repeated painful ulcers in the mouth. The ulcers are round or oval in shape and surrounded by inflammation. There are some problems and challenges in its treatment status. Although there are many treatment products on the market, there are still poor treatment effects and irritation or side effects during use, which bring additional pain to patients.
[0003] Bioactive glass, with its excellent antibacterial and anti-inflammatory properties and ability to promote tissue repair (by releasing beneficial ions such as calcium and silicon), has shown great potential in the field of oral and bone tissue defect repair. With the continuous innovation of material preparation technology, micro-nano bioactive glass has emerged. Its tiny particle size and high specific surface area give it a more superior biological effect. However, the use of these particles alone is often limited in practical applications. Therefore, it is particularly important to explore effective compounding and molding technologies.
[0004] As a mature micron-to-nanoscale fiber preparation process, electrospinning technology has become the preferred method for preparing high-performance nanofiber membrane materials due to its advantages such as simple equipment, low cost, strong process controllability and easy large-scale production. Through electrospinning, not only can the morphology and structure of the fiber be precisely controlled, but also the functional design of the material can be realized.
[0005] Chinese patent CN107185049A proposes a method for preparing a composite tissue repair material combining chitosan and bioactive glass, which involves the preparation of chitosan acetic acid solution, the preparation of bioactive glass solution and subsequent electrospinning. The addition of chitosan is intended to improve the mechanical strength of the material, while the bioactive glass focuses on improving its medical properties. Although the patent application claims that the prepared material has good mechanical properties, tissue repair ability and drug adhesion, there are still several key problems: (1) Insufficient mechanical strength: Although chitosan composite bioactive glass enhances the mechanical properties of the material to a certain extent, compared with some traditional biomaterials, especially in the repair area that needs to withstand higher stress, its mechanical strength may still be insufficient; (2) Lack of experimental verification: The patent description does not provide specific experimental data on the performance of the repair material, which makes it difficult to evaluate its actual effect and limits the credibility of the material in practical applications.
[0006] Therefore, in actual applications, it still faces limitations such as relatively insufficient mechanical strength and lack of sufficient experimental verification. In view of the current challenges and market demand for oral ulcer treatment materials, it is particularly urgent to develop a new oral repair material that not only has mechanical strength that can meet the needs of high-stress repair, but also has high antibacterial, anti-inflammatory and tissue regeneration capabilities. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing repair materials in practical applications, such as relatively insufficient mechanical strength and lack of sufficient experimental verification, and to provide a method for preparing an antibacterial repair film for oral ulcers.
[0008] The purpose of the invention is to provide an oral ulcer antibacterial repairing film.
[0009] Another object of the present invention is to provide application of the oral ulcer antibacterial repair membrane.
[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0011] The present invention provides a method for preparing an oral ulcer antibacterial repair film, comprising the following steps: thoroughly mixing a needle-shaped bioactive glass microsphere dispersion with gelatin and chitosan at 40-60° C. to obtain a mixed solution, and electrostatically spinning the obtained mixed solution to obtain an oral ulcer antibacterial repair film;
[0012] Wherein, the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is (0.5% to 5%): 1;
[0013] The needle-shaped bioactive glass microspheres include the following components in molar fractions: CaO 10% to 30%; SiO2 70% to 90%.
[0014] The present invention uses specific needle-shaped bioactive glass as an active ingredient and gelatin / chitosan as a composite carrier to prepare an oral ulcer antibacterial repair membrane by electrospinning. The resulting repair membrane is composed of gelatin-chitosan micro-nano fiber filaments and needle-shaped bioactive glass loaded therein. The needle-shaped bioactive glass microspheres are distributed on the fiber filaments, and the fiber diameter distribution is uniform and randomly interwoven, which can effectively load the needle-shaped bioactive glass microspheres. Specifically, the needle-shaped bioactive glass is formed by the accumulation of short needles and contains a large number of pore structures. Compared with traditional solid microspheres, it has a larger specific surface area, better dispersibility, and better fluidity. It also has excellent antibacterial, anti-inflammatory and damaged tissue repair performance, which is conducive to its synergistic antibacterial and anti-inflammatory effects with the gelatin-chitosan composite carrier; and the resulting composite membrane material has improved mechanical strength, which is particularly suitable for application in repair sites that need to withstand higher stresses, such as the oral site.
[0015] Furthermore, the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is (0.5%-5%):1; that is, the ratio of the mass of the needle-shaped bioactive glass microspheres to the total mass of gelatin and chitosan is (0.5%-5%):1.
[0016] Specifically, in the present invention, the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan can be 0.5%:1, 0.8%:1, 1%:1, 1.2%:1, 1.5%:1, 2%:1, 3%:1, 5%:1, etc., or an interval range formed by any of the above values, for example, (0.5%~1.2%:1, (0.8%~1.5%):1, (2%~3%):1, (0.5%~5%):1, etc., but not limited to this.
[0017] Preferably, the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is (0.5% to 3%):1.
[0018] More preferably, the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is (0.8% to 2%):1.
[0019] Further more preferably, the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is (0.8% to 1.2%):1.
[0020] Preferably, the needle-shaped bioactive glass microspheres include the following components in molar fractions: CaO 10% to 20%; SiO2 80% to 90%.
[0021] Furthermore, the temperature for sufficient mixing is 40-60° C., the manner for sufficient mixing is stirring, the stirring speed is 300-600 rpm, and the stirring time is 30-120 min.
[0022] Furthermore, the conditions for the electrospinning are: working voltage: 10-30 kV; receiving distance: 10-15 cm; injection rate: 0.2-1.0 mL / h.
[0023] Furthermore, the method for preparing the needle-shaped bioactive glass microspheres comprises the following steps:
[0024] S1. Mix ethanol, water and ammonia water according to volume ratio and mix thoroughly to obtain a mixed solution A;
[0025] S2: Mix ethanol and silicon source according to volume ratio and mix thoroughly to obtain mixed solution B;
[0026] S3. Pour the mixed solution A obtained in step S1 into the mixed solution B obtained in step S2, mix well, and obtain a suspension C;
[0027] S4. Add the calcium source to the suspension C obtained in step S3, mix thoroughly, age, wash with alcohol, dry and heat-treat to obtain needle-shaped bioactive glass microspheres.
[0028] Furthermore, in step S4, the temperature of the heat treatment is 600-700° C., more preferably 650-700° C.; the time of the heat treatment is 0.8-3 h, more preferably 1-2 h.
[0029] Furthermore, in step S4, the drying is freeze-drying.
[0030] Furthermore, in step S4, the aging time is 18 to 36 hours, more preferably 22 to 30 hours.
[0031] Furthermore, it is characterized in that the silicon source is organic silicon ester.
[0032] Preferably, the organic silicone ester is selected from ethyl orthosilicate and / or methyl orthosilicate.
[0033] Preferably, the calcium source is selected from calcium nitrate, calcium chloride or hydrates of the above calcium salts.
[0034] Preferably, the mass ratio of chitosan to gelatin is 1:(1-3), more preferably 1:(1.5-2.5). The degradation rate of gelatin is relatively fast, but by introducing chitosan into gelatin and utilizing the intermolecular forces between them, the degradation time of the composite membrane can be effectively adjusted. The repair membrane prepared using this ratio has a suitable degradation rate.
[0035] Preferably, in step S1, the volume ratio of the aqueous ammonia, ethanol and water is 1:(2-4):(0.5-2), more preferably 1:(3-4):(0.8-1.2).
[0036] Preferably, in step S2, the volume ratio of the silicon source to ethanol is 1:(6-9), more preferably 1:
[0037] (7~8).
[0038] Preferably, in step S4, the molar ratio of the silicon source to the calcium source is 1:(0.3-2), more preferably 1:(0.6-0.8).
[0039] Furthermore, the solvent of the bioactive glass microsphere dispersion is an acidic reagent.
[0040] Preferably, the acidic agent is acetic acid.
[0041] Furthermore, the mass concentration of the bioactive glass microsphere dispersion is 0.6 to 6 mg / mL, preferably 0.6 to 3.6 mg / mL, more preferably 0.96 to 2.4 mg / mL, and even more preferably 0.96 to 1.44 mg / mL.
[0042] Furthermore, the particle size of the needle-shaped bioactive glass microspheres is about 300 to 1000 nm.
[0043] Furthermore, the fiber diameter of the oral ulcer antibacterial repair membrane is about 300 to 1000 nm.
[0044] The present invention protects the oral ulcer antibacterial repairing film prepared by the preparation method.
[0045] The present invention also protects the use of the oral ulcer antibacterial repair film in the preparation of oral medical materials for treatment.
[0046] Furthermore, the oral ulcer antibacterial repair film can inhibit the growth of oral bacteria.
[0047] Furthermore, the oral bacteria include Porphyromonas gingivalis.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] The present invention utilizes specific needle-shaped bioactive glass as an active ingredient and gelatin / chitosan as a composite carrier to prepare an oral ulcer antibacterial repair membrane by an electrospinning method. The needle-shaped bioactive glass in the obtained repair membrane has excellent antibacterial, anti-inflammatory and damaged tissue repair properties; at the same time, the electrospun micro-nano fiber network structure constructed based on gelatin-chitosan meets the requirements of autonomously adjustable mechanical properties and suitable degradation rate, providing patients with a safer and more comfortable treatment experience; and the preparation process of the obtained composite membrane is simple, uses an aqueous non-toxic solvent, is low in cost, can be mass-produced, and is expected to be applied to the field of oral ulcer repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a scanning electron microscope image of the needle-shaped bioactive glass microspheres provided by the present invention.
[0051] Figure 2 The scanning electron microscope images of the composite membranes obtained in Example 1 (1 wt% MNBG) of the present invention, Comparative Examples 1-2 (0 wt% MNBG, (10 wt% MNBG) are shown.
[0052] Figure 3The figures are the mechanical property test graphs of the composite films obtained from Example 1 (1% MNBG) of the present invention, Comparative Examples 1-2 (0% MNBG, (10% MNBG), wherein the left figure is the tensile stress-tensile strain graph of the composite films of the three sample groups, and the right figure is the tensile stress statistical graph of the composite films of the three sample groups at the fracture point (i.e., the peak value in the left figure); * indicates P<0.05.
[0053] Figure 4 This is a statistical graph of the antibacterial experimental results of the needle-shaped bioactive glass microspheres provided by the present invention.
[0054] Figure 5 The present invention provides a statistical graph of the results of the anti-inflammatory experiment of the needle-shaped bioactive glass microspheres, wherein Figure A shows the morphology of RAW264.7 cells co-cultured with the needle-shaped bioactive glass microspheres for one day; Figure B is a microscopic image of MNBG micro-nanoparticles being endocytosed into the cytoplasm by cells; Figure C is a statistical graph of the effect of MNBG on the activity and proliferation of RAW cells; Figure D is a statistical graph of the effect of MNBG on the mRNA expression levels of IL-β, IL-6, TNF-α and iNOS in RAW cells; wherein * indicates P<0.05. DETAILED DESCRIPTION
[0055] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0056] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0057] Example 1 Preparation of needle-shaped bioactive glass microspheres
[0058] In the needle-shaped bioactive glass microspheres provided in this embodiment, the molar fraction of CaO is 20% and the molar fraction of SiO2 is 80%. The amount of each raw material used is: 15 mL of anhydrous ethanol, 5 mL of deionized water, and 5 mL of ammonia water in step S1; 15 mL of anhydrous ethanol and 2 mL of tetraethyl orthosilicate (i.e., 8.92 mmol) in step S2; and the amount of calcium nitrate tetrahydrate used is 1.6 g (specifically 6.73 mmol).
[0059] The preparation method is as follows:
[0060] S1. Add anhydrous ethanol, deionized water and ammonia water into a 100 mL beaker, place on a magnetic stirrer, and stir for 40 min until a homogeneous transparent solution A is obtained at a stirring speed of 500 rpm;
[0061] S2. Anhydrous ethanol and tetraethyl orthosilicate were added to a 100 mL beaker in sequence, placed on a magnetic stirrer, and stirred for 40 min until a uniform and transparent solution B was obtained. The stirring speed was 500 rpm.
[0062] S3. The solution A obtained in step S1 was quickly added to the solution B obtained in step S2 to form a suspension C, and the stirring speed was 900 rpm and the stirring was continued for 1.5 hours;
[0063] S4. After adding calcium nitrate tetrahydrate to the suspension C obtained in step S3, stirring was continued for 1 hour, ultrasonication was performed for 30 minutes, and aging was performed for 1 day. The suspension was washed with ethanol three times, freeze-dried, and heat-treated at 680° C. for 1 hour to obtain needle-shaped bioactive glass microspheres.
[0064] Example 2 Needle-shaped bioactive glass / gelatin / chitosan composite membrane and preparation method thereof
[0065] In the needle-shaped bioactive glass microspheres / gelatin / chitosan composite film provided in this embodiment, the mass ratio of needle-shaped bioactive glass microspheres to gelatin-chitosan is 1:100, and the amounts of each raw material are: 12.0 mg needle-shaped bioactive glass microspheres, 800.0 mg gelatin, 400.0 mg chitosan, and 10.0 mL acetic acid.
[0066] The preparation method is as follows:
[0067] (1) Disperse 12.0 mg of needle-shaped bioactive glass microsphere powder in 10.0 mL of acetic acid solution, stir at 300 rpm for 30 min, and ultrasonically vibrate for 10 min until uniform, to obtain solution A;
[0068] (2) adding 800.0 mg of gelatin particles to the solution A obtained in step (1), heating at 50° C. and stirring at 500 rpm for 120 min until completely dissolved, to obtain a mixed solution B;
[0069] (3) adding 400.0 mg of chitosan particles to the mixed solution B obtained in step (2), heating at 50° C. and stirring at 500 rpm; stirring for 120 min until completely dissolved, to obtain a mixed solution C;
[0070] (4) Spinning the mixed solution C obtained in step (3) in an electrospinning machine, adjusting the voltage to 30 kV and the receiving distance to 15 cm; the injection rate is 0.6 mL / h, and obtaining a needle-shaped bioactive glass microsphere / gelatin / chitosan composite film.
[0071] Example 3 Needle-shaped bioactive glass microsphere / gelatin / chitosan composite film and preparation method thereof
[0072] The difference from Example 2 is that the added amount of the needle-shaped bioactive glass microspheres is 6.0 mg, so that the mass ratio of the needle-shaped bioactive glass to gelatin-chitosan is 0.5:100.
[0073] The other steps and parameters are the same as those in Example 2.
[0074] Example 4 Needle-shaped bioactive glass microsphere / gelatin / chitosan composite film and preparation method thereof
[0075] The difference from Example 2 is that the added amount of the needle-shaped bioactive glass microspheres is 60 mg, so that the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is 5:100.
[0076] The other steps and parameters are the same as those in Example 2.
[0077] Comparative Example 1 Gelatin / chitosan composite film and preparation method thereof
[0078] The difference from Example 2 is that the added amount of needle-shaped bioactive glass microspheres is 0 mg.
[0079] The other steps and parameters are the same as those in Example 2.
[0080] The specific raw materials include the following ingredients:
[0081] In the gelatin / chitosan composite film provided in this comparative example, the mass ratio of needle-shaped bioactive glass microspheres to gelatin-chitosan is 0:100, and the amounts of each raw material are: 0.0 mg needle-shaped bioactive glass microspheres, 800.0 mg gelatin, 400.0 mg chitosan, and 10.0 mL acetic acid.
[0082] The preparation method is as follows:
[0083] (1) 800.0 mg of gelatin particles were added to 10.0 mL of acetic acid solution, heated at 50° C., and stirred at 500 rpm for 120 min until completely dissolved to obtain a mixed solution A;
[0084] (2) adding 400.0 mg of chitosan particles to the solution A obtained in step (1), heating at 50° C., stirring at a speed of 500 rpm, and stirring for 120 min until completely dissolved, to obtain a mixed solution B;
[0085] (3) Spinning the mixed solution B obtained in step (2) in an electrospinning machine, adjusting the voltage to 30 kV and the receiving distance to 15 cm; the injection rate is 0.6 mL / h, and a gelatin / chitosan composite membrane material is obtained.
[0086] Comparative Example 2 Needle-shaped bioactive glass microsphere / gelatin / chitosan composite film and preparation method thereof
[0087] The difference from Example 2 is that the added amount of the needle-shaped bioactive glass microspheres is 120 mg, so that the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is 10:100.
[0088] The other steps and parameters are the same as those in Example 2.
[0089] Experimental Example Test Characterization of Composite Membrane
[0090] The composite membrane obtained in Example 2 was used as a representative composite membrane in the examples and the composite membranes obtained in Comparative Examples 1 to 2 were tested for performance.
[0091] (1) Microscopic morphology analysis
[0092] The scanning electron microscope image of the needle-shaped bioactive glass microspheres provided in Example 1 of the present invention is as follows: Figure 1 As shown, it can be seen that the micro-nano bioactive glass microspheres are mainly composed of the accumulation of needle-shaped bioactive glass. The particles are spherical, evenly dispersed, and a large number of accumulated pore structures are distributed on the surface.
[0093] The scanning electron microscopy images of the composite membranes obtained in Example 2 (1 wt% MNBG) and Comparative Examples 1-2 (0 wt% MNBG and 10 wt% MNBG) are as follows: Figure 2 As shown, the obtained composite fiber membrane is composed of gelatin / chitosan fibers with a diameter of about 500 nm. In the sample with the addition of MNBG, needle-shaped bioactive glass microspheres with a diameter of about 300 nm can be seen attached to the fiber filaments.
[0094] The composite membranes obtained in Examples 3 to 4 have substantially the same morphology as that of Example 2, and will not be described in detail herein.
[0095] (2) Mechanical properties test
[0096] Example 2, Comparative Examples 1-2 Mechanical properties of the composite membrane obtained - tensile test results are as follows Figure 3 As shown, the composite membrane obtained in Example 1 (1% MNBG) has the best tensile properties, which is significantly higher than the other two, and has good mechanical strength. This shows that the tensile properties of the gelatin-chitosan composite fiber membrane can be enhanced after the appropriate amount of needle-shaped bioactive glass microspheres are added. Not adding or adding excessive needle-shaped bioactive glass microspheres is not conducive to improving the mechanical strength of the obtained composite membrane.
[0097] The tensile properties of the composite films obtained in Examples 3 to 4 are better than those in Comparative Examples 1 to 2, and have mechanical property test results close to those of Example 2, which will not be described in detail here.
[0098] (3) Antibacterial test
[0099] 1. Experimental methods
[0100] The present invention uses Porphyromonas gingivalis (P.gingivalis) as an experimental model. The PBS solution of needle-shaped bioactive glass microspheres MNBG in the experimental group is transferred to brain heart infusion broth, wherein the final working concentration of MNBG in the broth is 10 mg / mL. The blank group is conventionally cultured. In an anaerobic environment at 37°C, Porphyromonas gingivalis is cultured on brain heart infusion (BHI) agar plates containing / not containing MNBG (10 6 ~10 7 CFU mL -1 ), and 24 hours later, bright field photography was taken to observe the bacterial growth.
[0101] 2. Experimental results
[0102] The antibacterial test results of the needle-shaped bioactive glass microspheres (MNBG) of the present invention are as follows: Figure 4 As shown in the figure, the results of the co-culture experiment of MNBG and Porphyromonas gingivalis showed that the MNBG group had a significant antibacterial effect compared with the blank control group.
[0103] (4) In vitro anti-inflammatory ability
[0104] 1. Experimental methods
[0105] The present invention uses mouse macrophage cell line RAW 264.7 (abbreviated as RAW) cells to study the anti-inflammatory effect of micro-nano bioactive glass MNBG. RAW cells are cultured in a high-glucose DMEM medium supplemented with 10% fetal bovine serum and 1% penicillin / streptomycin, and the medium is replaced every 2 days. After RAW cells are co-cultured with 100μg / mL needle-shaped bioactive glass for 1 day, scanning electron microscope and confocal microscope are used for photography and observation, respectively, wherein the cell nucleus is stained with 4',6-diamidino-2-phenylindole (DAPI) to show blue, MNBG microspheres labeled with fluorescein isothiocyanate (FITC) to show green, and the cytoplasm is stained with phalloidin to show red. The detection of cell activity and proliferation can intuitively reflect the growth state of cells under material stimulation, and is a basic method for evaluating material toxicity. The experiment selects different concentrations of needle-shaped bioactive glass to co-culture with RAW cells for 1 day, and detects cell activity and proliferation by CCK-8 method. In order to simulate the inflammatory response in vitro, lipopolysaccharide (LPS, 100 ng / mL) was added to the culture medium and incubated for 24 hours to polarize it to the pro-inflammatory M1 phenotype. The culture medium was then replaced with complete culture medium containing 100 μg / mL MNBG and cultured for another 24 hours. Finally, RT-qPCR was used to detect the mRNA expression levels of IL-β, IL-6, TNF-α and iNOS in RAW cells to verify their anti-inflammatory effect.
[0106] 2. Experimental results
[0107] The results of the in vitro anti-inflammatory test of the needle-shaped bioactive glass microspheres provided in Example 1 of the present invention are as follows: Figure 5 As shown, Figure 5 Figure A shows that after RAW264.7 cells were co-cultured with needle-shaped bioactive glass microspheres for 1 day, the cells were well spread. Figure 5 Panel B in the figure shows that after one day of co-culture, MNBG micro-nanoparticles were endocytosed into the cytoplasm by cells; Figure 5 The CCK-8 experimental results in Figure C prove that MNBG has good cell proliferation-promoting properties; Figure 5 The RT-qPCR experimental results in Figure D showed that MNBG has the ability to significantly downregulate the expression of pro-inflammatory related genes.
[0108] From the above, it can be seen that the needle-shaped bioactive glass microspheres obtained in the present invention are formed by stacking short needles and contain a large number of pore structures. Compared with traditional solid microspheres, they have a larger specific surface area, better dispersibility, better bioactivity and fluidity. Through electrospinning technology, the needle-shaped bioactive glass microspheres can be loaded on gelatin-chitosan micro-nano fiber filaments to obtain a composite membrane, specifically, the needle-shaped bioactive glass microspheres are distributed on the fiber filaments, the fiber diameter distribution is uniform, and it is randomly interwoven, which can effectively load the needle-shaped bioactive glass microspheres; in vitro data show that the obtained needle-shaped bioactive glass microspheres have significant antibacterial and anti-inflammatory capabilities, which is beneficial for it to synergistically exert antibacterial and anti-inflammatory effects with the composite carrier, and the obtained composite membrane has improved mechanical strength, which is particularly suitable for application in repair areas that need to withstand higher stresses, such as the oral area.
[0109] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing an oral ulcer antibacterial repair film, characterized in that: The steps include: S1. The needle-shaped bioactive glass microsphere dispersion is thoroughly mixed with gelatin and chitosan to obtain a mixed solution, and the obtained mixed solution is electrospinned to obtain an oral ulcer antibacterial repair membrane; Wherein, the mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is (0.5% to 5%): 1; The needle-shaped bioactive glass microspheres comprise the following components in molar fractions: CaO 10% to 30%; SiO2 70% to 90%.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the needle-shaped bioactive glass microspheres to gelatin-chitosan is (0.5% to 3%):
1.
3. The preparation method according to claim 1, characterized in that: The method for preparing the needle-shaped bioactive glass microspheres comprises the following steps: S1. Mix ethanol, water and ammonia water according to volume ratio and mix thoroughly to obtain a mixed solution A; S2: Mix ethanol and silicon source according to volume ratio and mix thoroughly to obtain mixed solution B; S3. Pour the mixed solution A obtained in step S1 into the mixed solution B obtained in step S2, mix well, and obtain a suspension C; S4. Add the calcium source to the suspension C obtained in step S3, mix thoroughly, age, wash with alcohol, dry and heat-treat to obtain needle-shaped bioactive glass microspheres.
4. The preparation method according to claim 3, characterized in that: In step S4, the temperature of the heat treatment is 600-700°C.
5. The preparation method according to claim 3, characterized in that: The silicon source is organic silicon ester.
6. The preparation method according to claim 3, characterized in that: The calcium source is selected from calcium nitrate, calcium chloride or hydrates of the above calcium salts.
7. The preparation method according to claim 1, characterized in that: The mass ratio of chitosan to gelatin is 1:(1-3).
8. The preparation method according to claim 1, characterized in that: The solvent of the needle-shaped bioactive glass microsphere dispersion is an acidic reagent.
9. The oral ulcer antibacterial repairing film prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the oral ulcer antibacterial repair film according to claim 9 in the preparation of oral medical materials for treatment.
Citation Information
Patent Citations
Preparation method of chitosan composite bioactive glass tissue repairing material
CN107185049A